Analisis Pesan Dakwah Dalam Buku Muhammad Al-Fatih 1453 Karya Ustadz Felix Y. Siauw - Berlian Rahmansyah; Nurseri Hasnah Nasution; Emi Puspita Dewi (Social Science and Contemporary Issues Journal, 2024)
This study is entitled "Analysis of Da'wah Messages in the Book of Muhammad Al-Fatih 1453 by Ustadz Felix. Y Siauw.” In the current era of globalization, many people or ustadz preach through bi al-qalam (writing), including Ustadz Felix Y. Siauw who preaches through writing. Da'wah through writing has advantages compared to other methods, including: the work of an author will be known forever, even when the author is gone, because readers will always remember the messages contained in these books. The work of Felix Y. The purpose of this study was to find out what messages the da'wah conveyed by Ustadz Felix Y. Siauw in the book Muhammad Al-Fatih 1453, both in the messages of aqidah, moral messages, and shari'ah messages. Researchers also find out which messages are more dominant in this book so that researchers can conclude what the contents of this thesis are. Writing this thesis using a qualitative approach to the method of content analysis. Content analysis is research that is an in-depth discussion of the contents of written or printed information in the mass media. Based on the results of the data obtained, it is found that the contents of the book Muhammad Al-Fatih 1453 contain many da'wah messages including: messages of faith, moral messages and sharia messages that are related to everyday life. The most dominant da'wah message in this book is about Aqidah, how Muhammad Al-Fatih's belief in the promise that Allah and the Messenger of Allah gave in his bisyaroh in the form of the conquest of the city of Constantinople which became a separate strength for Muhammad Al-Fatih and his troops to realize the bisyaroh that the Messenger of Allah conveyed.